Verici alıcı çeşitlemesi - Fidan, Efendi (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2010)
Telsiz haberleşmede sönümlemenin işareti kötüleştirici etkisini azaltmak için kullanılan çeşitlemelerden uzay çeşitlemesi (verici anten ve alıcı anten seçiminin birleştirilmesi, verici anten seçimi ve alıcıda maksimum oranlı birleştirmesinin uygulanması, genelleştirilmiş alıcı anten seçimini ile verici anten ve genelleştirilmiş alıcı anten seçiminin birleştirilmesi) Rayleigh ve Nakagami-m kanalda incelendi. Mevcut analizler moment üretici fonksiyon (MÜF) metodu kullanılarak yeniden düzenlendi. Elde edilen sonuçların mevcut olanlardan karmaşıklık bakımından daha sade olduğu gösterildi. Mevcut ve yeni analizler kullanılarak M'li Faz Kaydırmalı Anahtarlama (M-FKA) ve M'li Dörtlü Genlik Modülasyonu (M-DÖGM) için birçok farklı durumların ortalama Sembol Hata Olasılığı (SHO) eğrileri elde edildi. Özellikle Rayleigh kanalda verici anten seçimi ve genelleştirilmiş alıcı anten seçiminin birleştirilmesi için elde edilen sonuçların mevcut olanlardan hesaplama karmaşıklığı bakımından daha avantajlı ve basit olduğu gösterilmiştir. Aynı şekilde hem Rayleigh kanalda hem de Nakagami-m kanalda m tam sayı değerleri için verici anten seçimi ve alıcıda maksimum oranlı birleştirme durumu için MÜF kullanılarak elde edilen sonuçların mevcut olanlardan daha sade olduğu gösterildi. Nakagami-m kanalda verici ve alıcı anten seçiminin birleştirilmesi için MÜF metodu kullanılarak genelleştirilmiş ortalama SHO denklemleri elde edildi. Bunun yanında Nakagami-m kanal için genelleştirilmiş alıcı anten seçiminin MÜF'si yeniden düzenlenerek bu senaryonun genelleştirilmiş ortalama SHO denklemleri elde edildi. Son olarak Nakagami-m kanalda verici anten ve genelleştirilmiş alıcı anten seçiminin birleştirilmesinin özel bir durumu için analitik SHO elde edildi.

In wireless communications, in order to overcome the drawbacks of fading, different types of diversity solutions are proposed. Space diversity is one of these proposed methods. In this work, attention is paid on the types of space diversity over Rayleigh and Nakagami-m fading channels. In particular, combined transmit and receive antenna selection, transmit antenna selection and maximum ratio combining, generalized receive antenna selection and combined transmit antenna selection and generalized receive antenna selection are investigated. Existing performance analyses are reformulated by usage of moment generating function approach. Obtained results are simpler and more compact than the existing ones. To verify the accuracy of obtained results, different curves of average symbol error rates of various cases for M-PSK and M-QAM are obtained by usage of the available and obtained expressions of symbol error rates. In particular, it is proven that reformulation of performance analysis of the combined transmit antenna selection and generalized receive antenna selection over Rayleigh fading channel reduces computational complexity and obtained results are simpler than the existing ones. Similarly, in both Rayleigh and Nakagami-m fading channels, expressions of average symbol error rates for transmit antenna selection and maximum ratio combining based on moment generating function approach are obtained. These results are also more compact and simpler than the existing ones. The simulation results of the obtained expressions for different cases are illustrated in details. The joint transmit and the receive antenna selection over Nakagami-m fading channel is considered and for integer values of fading parameter m expressions of the average symbol error rates are obtained based on moment generating function approach. Lastly, a special case of the combined transmit antenna selection and generalized receive antenna selection over Nakagami-m fading channel is investigated.
Transmit receive diversity
Keywords: Elektrik ve Elektronik Mühendisliği; Electrical and Electronics Engineering